Communicating coping during the pandemic: an analysis of the presidential addresses of Ghana and Nigeria during the COVID-19 pandemic - Eshun, Ernest Ansah; Olajire, Abigail; Akheituame, Esther (Frontiers in Communication, 2024)
Coping is a well-studied concept across multiple disciplines, including communication and psychology. Over the years, studies have identified that individuals and organizations use varying coping strategies to deal with an unpleasant phenomenon. This paper analyzed themes of coping within the presidential addresses of Ghana and Nigeria during the COVID-19 pandemic.We argued that an investigation into these important official documents from the two Global South countries could offer propagative ideas for the communication subareas of health communication, mass communication, disaster, and crisis communication. After analyzing the presidential addresses, the study identified emerging patterns of African communication systems, social comparison, and politico-religious communication as coping themes embedded in the speeches. The role of the African communication system and implications for collective coping, cultural values, and local resources as agents for national coping strategy are discussed.